2019
DOI: 10.1108/ijchm-03-2017-0136
|View full text |Cite
|
Sign up to set email alerts
|

How does consumer regulatory focus impact perceived value and consumption emotions?

Abstract: Purpose This study aims to investigate how individuals’ regulatory focus affects perceived value and consumption emotions and how differently perceived value and emotions influence the future behavioral intentions of ethnic restaurant customers. Design/methodology/approach The proposed model was empirically tested with the online survey sent to frequent American travelers who have had dining experiences at Asian restaurants. A total of 435 valid responses were obtained and analyzed by means of structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 67 publications
4
32
0
2
Order By: Relevance
“…Different regulatory focus types imply different sensitivities to information about an emotion ( Shah and Higgins, 2001 ). Promotion-focused individuals pursue growth-related outcomes and are more likely to experience happiness, while prevention-focused individuals pursue safety-related outcomes and are more likely to experience sorrow ( Higgins, 1998 ; Ouyang et al, 2015 ; Song and Qu, 2019 ). Previous studies found that promotion focus can induce heuristic processing, which enables people to make judgments based on subjective emotions, while prevention focus can induce analytic processing, which promotes judgments less based on subjective emotions ( Friedman and Förster, 2000 , 2001 ; Pham et al, 2001 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Different regulatory focus types imply different sensitivities to information about an emotion ( Shah and Higgins, 2001 ). Promotion-focused individuals pursue growth-related outcomes and are more likely to experience happiness, while prevention-focused individuals pursue safety-related outcomes and are more likely to experience sorrow ( Higgins, 1998 ; Ouyang et al, 2015 ; Song and Qu, 2019 ). Previous studies found that promotion focus can induce heuristic processing, which enables people to make judgments based on subjective emotions, while prevention focus can induce analytic processing, which promotes judgments less based on subjective emotions ( Friedman and Förster, 2000 , 2001 ; Pham et al, 2001 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Marketing literature often emphasizes the necessity of utilitarian values more inevitable practical properties, potentially including both loss and gain, while the hedonic value is more pleasure-oriented, and empirical attributes only provide profit [2,25]. Chernev (2004) argued that promotion-focused goals are better matched with hedonic value, while a prevention focus is more likely to fit utilitarian value [2,26]. Also, Hong, Lin, & Hsieh (2017) argued that the hedonic and utilitarian values had a significant impact on customers' intention to continue using the smartwatch [4].…”
Section: Perceived Value (Utilitarian/hedonic)mentioning
confidence: 99%
“…At the beginning of the 21st century, blogs became one of the most popular social media formats. People could communicate by posting an article online or providing feedback as readers [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Through this research, a model with these variables was proposed because there is a synergistic effect between them. The approach rests with the effects of food values and positive early emotions directed towards the form of the attitude as a predecessor of the purchase intention [12,13,14]. This model was designed from the separation of attitudes: one directed towards the act of eating and another towards the brand.…”
Section: Introductionmentioning
confidence: 99%